(untitled) (Semiárida, 2020)
The algarrobo tree forest of Mendoza presents a number of stable states of low productivity with a high presence of shrubs. In this situations, the use of roller chopping, as a tool to control the shrubs population, improves this environments. Sowing exotic species with roller chopping to enrich the range has been conducted in Mendoza with different results. Species like pasto llorón (Eragrostis curvula Nees.) and digitaria (Digitaria eriantha Steudel.) require rainfalls of 400 to 600 mm, while buffel grass (Cenchrus ciliaris L.) does not tolerate low temperatures. Therefore, adapted germoplasm to cold arid zones is needed. The objective of this study was to evaluate the establishment of pasto plumerito (Trichloris crinita Parodi) with roller chopping using buffel grass as a dispersion vehicle. Two treatments were compared: pasto plumerito and buffel grass sowed with roller chopping (TS) and the control without sowing and roller chopping. The sowing density was 2 kg of pasto plumerito seeds with 5 kg of buffel grass. Seedlings density was 1,4 and 0,9 pl/m2 for pasto plumerito and buffel grass, respectively. The buffel grass was a good dispersion vehicle to pasto plumerito seeds, giving a fast cover the first year of the implantation and acting as a cover crop.